An industrial control study on Alaska Milk Corporation - De Castro, Diana May (College of Engineering, 2006)
The Alaska Milk Corporation is one of the two major milk companies in the Philippines. Currently, Alaska is maintaining brand leadership in the liquid canned milk category and holding a strong and growing position in powdered milk. The company is securing the quality of the milk they are producing to satisfy the Filipino consumers and be the best in this field. Problems are detected to be occurring frequently in the manufacturing of liquid milk and thus the company is seeking for an Industrial Quality Control study. Data was gathered by conducting interview with the Quality Assurance Department and liquid milk manager. An actual observation in the plant was also done to be familiar with the process. The problems identified were undesirable viscosity, brix and percent fat. The three were considered because they have the highest percentage of samples that falls out the specification limit. The other parameters were not evaluated because they were not normally distributed. Using the Individuals control charts and Moving-Range control charts. it was found out that there were points out of the upper and lower limits. The process was out of control. The control limits were found to be too wide for the process as well as signs of possible shift in the process average were detected. In order to determine the capability of the processes, the points that showed signs of the presence of assignable causes of variation were discarded in order to achieve an in control process. The control charts are then modified. Process capability was then computed. The following are the process capability for each parameter: 0.54 for viscosity of Sweetened condensed Milk (SCM), 0.34 for degree brix of Sweetened Condensed Creamer (ASADA), 0.84 for viscosity of ASADA, and 0.71 for percent fat of ASADA. The process capability values show that the process is inadequate which means that the company should take immediate action on re-examine their process.